1998
DOI: 10.2169/internalmedicine.37.880
|View full text |Cite
|
Sign up to set email alerts
|

Left Postpneumonectomy Syndrome Successfully Treated with Endobronchial Stent.

Abstract: Wedescribe a case of left pneumothorax-induced left postpneumonectomy syndrome in the absence of anatomical anomalies developing at 10 years after the operation. Weplaced an endobronchial stent into the right truncus intermidius and the procedure resulted in recovery of the syndrome. We consider endobronchial stent placement as an effective treatment for postpneumonectomy syndrome, especially when surgical management is not feasible. (Internal Medicine 37: 880-883, 1998)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…of patients) OCEBM score Harney et al [ 12 ] 1 Metallic stent 49 y LRTI 30 mo Good Y: re-stenting 4 Moser et al [ 14 ] 1 Silastic stent 12 y Good 5 mo Died: alcohol intoxication and aspiration N 4 Abe et al [ 17 ] 1 2 metallic stents 3 y Good 12 y Recurrent LRTIs. Died—respiratory failure N 4 Nakamura et al [ 13 ] 1 Balloon dilation 10 y Poor; stent inserted 3 mo Died–MI N 4 Cordova et al [ 30 ] 1 2 metallic stents 4 y Good 1 y Good N 4 Stratakos et al [ 38 ] 1 Metallic stent 2 y Poor 6 mo Died–PE Y: silastic stent insertion 4 mo Months; y Years OCEMB Score: 1a—SR of RCTs;...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…of patients) OCEBM score Harney et al [ 12 ] 1 Metallic stent 49 y LRTI 30 mo Good Y: re-stenting 4 Moser et al [ 14 ] 1 Silastic stent 12 y Good 5 mo Died: alcohol intoxication and aspiration N 4 Abe et al [ 17 ] 1 2 metallic stents 3 y Good 12 y Recurrent LRTIs. Died—respiratory failure N 4 Nakamura et al [ 13 ] 1 Balloon dilation 10 y Poor; stent inserted 3 mo Died–MI N 4 Cordova et al [ 30 ] 1 2 metallic stents 4 y Good 1 y Good N 4 Stratakos et al [ 38 ] 1 Metallic stent 2 y Poor 6 mo Died–PE Y: silastic stent insertion 4 mo Months; y Years OCEMB Score: 1a—SR of RCTs;...…”
Section: Resultsmentioning
confidence: 99%
“…Four of the 6 patients died during the follow-up period; one died of a PE and the other of respiratory failure 6 months and 12 years later, respectively [ 37 , 38 ]. Nakamura et al reported a case of endobronchial stenting following failed endobronchial balloon dilation with limited follow-up [ 13 ]. Moser et al described the successful use of a silastic stent with limited follow-up (n = 1) [ 14 ] (Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported several articles on the treatment of PPS, including tissue expander implantation [ 3 6 ], gas injection [ 7 , 8 ] and stenting [ 9 ]. Unfortunately, tissue expanders for thoracic cavity stabilization are not approved for use in Japan due to insurance regulations, which limits their availability for emergency surgery.…”
Section: Discussionmentioning
confidence: 99%
“…El diagnóstico exige una historia clínica detallada, examen físico, radiografías de tórax, tomografía computada, pruebas de función pulmonar y broncoscopia; una vez establecido, el tratamiento continúa siendo un desafío. 1-4.6 Los tutores endoluminales (stents) de silastic tienen la ventaja de su fácil adecuación, reposición y remoción, 8,9 pero se han comunicado, como inconvenientes mayores, la migración y la obstrucción. Los tutores metálicos autoexpandibles tienen la ventaja de una fácil inserción, conformación a la vía aérea y estabilidad.…”
Section: Discussionunclassified